Resection of Cavity Shave Margins in Stage 0–III Breast Cancer Patients Undergoing Breast Conserving Surgery: A Prospective Multicenter Randomized Controlled Trial. Issue 5 (8th May 2021) - Dupont, Elisabeth; Tsangaris, Theodore; Garcia-Cantu, Carlos; Howard-McNatt, Marissa; Chiba, Akiko; Berger, Adam C.; Levine, Edward A.; Gass, Jennifer S.; Gallagher, Kristalyn; Lum, Sharon S.; Martinez, Ricardo D.; Willis, Alliric I.; et al.
Abstract : Objective: Single-center studies have demonstrated that resection of cavity shave margins (CSM) halves the rate of positive margins and re-excision in breast cancer patients undergoing partial mastectomy (PM). We sought to determine if these findings were externally generalizable across practice settings. Methods: In this multicenter randomized controlled trial occurring in 9 centers across the United States, stage 0–III breast cancer patients undergoing PM were randomly assigned to either have resection of CSM ("shave" group) or not ("no shave" group). Randomization occurred intraoperatively, after the surgeon had completed their standard PM. Primary outcome measures were positive margin and re-excision rates. Results: Between July 28, 2016 and April 13, 2018, 400 patients were enrolled in this trial. Four patients (2 in each arm) did not meet inclusion criteria after randomization, leaving 396 patients for analysis: 196 in the "shave" group and 200 to the "no shave" group. Median patient age was 65 years (range; 29–94). Groups were well matched at baseline for demographic and clinicopathologic factors. Prior to randomization, positive margin rates were similar in the "shave" and "no shave" groups (76/196 (38.8%) vs. 72/200 (36.0%), respectively, P = 0.604). After randomization, those in the "shave" group were significantly less likely than those in the "no shave" group to have positive margins (19/196 (9.7%) vs. 72/200 (36.0%), P < 0.001), and to require re-excision or mastectomy for margin clearance (17/196 (8.7%) vs. 47/200 (23.5%), P < 0.001). Conclusion: Resection of CSM significantly reduces positive margin and re-excision rates in patients undergoing PM.